Targeting agricultural research based on potential impacts on poverty reduction: strategic program priorities by agroecological zone in Nigeria - Alene, A.; Manyong, Victor M.; Tollens, E.F.; Abele, S. (Elsevier, 2007)
Growing concern for poverty in the face of declining agricultural research budgets has increasingly required formal priority setting of public agricultural research in developing countries to ensure that scarce research resources are allocated in ways that will have the greatest impact on the poor. This paper assessed the potential impacts of alternative commodity research programs on poverty reduction in three agro-ecological zones of Nigeria and identified strategic agricultural research priorities in the three zones. The paper discusses the poverty reduction-based priorities and their role in facilitating dialogue between research managers and policymakers aimed at sharpening the focus of agricultural research to achieve poverty reduction objectives in Nigeria.